The Influence of Control System Apparatus Competence Internal Supervision on Local Government Accountability - Abduh, Muahammad; Ramdhani, Rezah (Journal Development Manecos, 2025)
Research data demonstrates that internal controls together with apparatus competence and internal supervision function as influential factors leading to better government accountability. Internal control systems establish a direct positive relationship with the accountability of the Makassar City Regional Government due to proper execution of well-developed control frameworks. While the competence of the apparatus has a positive and significant effect on the accountability of the Makassar City Regional Government, this means that with good apparatus competence it will increase the accountability of the regional government in Makassar City and Internal supervision has a positive and significant effect on the accountability of the Makassar City Regional Government, this means that with the implementation of good internal supervision it will increase the accountability of the regional government in Makassar City.